2018
DOI: 10.1177/0340035218785196
|View full text |Cite
|
Sign up to set email alerts
|

Research data management and sharing among researchers in Arab universities: An exploratory study

Abstract: This study investigates researchers’ current practices for managing and sharing research data. An online survey was conducted among researchers from three Arab universities in Egypt, Jordan, and Saudi Arabia. In total, 337 participants filled out the questionnaire. The study shows that 97% of researchers were responsible for their research data, and 64.4% of researchers shared their data. Contributing to scientific progress and increasing research citations and visibility were the key factors that motivated re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 30 publications
6
42
0
Order By: Relevance
“…was produced by only one (0.8%) researcher. Previous studies (Kvale 2012;Buys and Shaw 2015;Elsayed & Saleh 2018;and Bezuidenhout & Chakauya 2018) also found similar to the current one. All these studies found that the majority of researchers produced standard office documents.…”
Section: Findings and Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…was produced by only one (0.8%) researcher. Previous studies (Kvale 2012;Buys and Shaw 2015;Elsayed & Saleh 2018;and Bezuidenhout & Chakauya 2018) also found similar to the current one. All these studies found that the majority of researchers produced standard office documents.…”
Section: Findings and Discussionsupporting
confidence: 91%
“…However, the researchers decided to use the data as the response rate was in line with several studies of a similar nature elsewhere. Buys and Shaw (2015), Wouters and Haak (2017), and Elsayed and Saleh (2018) also had lower response rates of 6.4%, 2.3% and 8% in studies similar to this one. Schöpfel and Prost (2016) point out that some of the similar studies' response rates are partially unknown as no one knows the whole population of the studies.…”
Section: Methodssupporting
confidence: 60%
See 3 more Smart Citations